Fluxos de dióxido de carbono e metano de um lixão na Amazônia - PINHEIRO, Layse Teixeira (Universidade Federal do Pará, 2019)
This work had as aim the quantification of greenhouse gases, carbon dioxide and methane from the uncontrolled Aurá landfill, known as the "Aurá Lode", in addition to collecting information from the place after its partial closure in 2015 .The research had a qualitative analysis of environmental aspects of the site and an experimental part, with the development of flow chambers, to capture the gases through the covering of cells other than the landfill. The measurements were performed in two ways, the first with 24 chambers distributed in three distinct points of two cells with relatively different ages and 90 chambers, distributed in grid, in a closed cell. These measurements occurred in a less rainy period and had their points located through geographic coordinates. A portable gas analyzer was used to simultaneously obtain the gas concentration in ppm. The flow calculations involved the selection of the intervals of each chamber, determination of the regression line of the gas concentrations by time, barometric equation and insertion of the data obtained in the main flow equation. The values of methane emissions in the cells titled A, B and C were 191,226 g m² d-¹, 397.7 g m² d-¹ and 36.30 g m² d-¹, respectively. The carbon dioxide fluxes reached 10,554.1 g m² d-¹, 11,786.65 g m² d-¹ and 7,529.77 g m² d-¹.